TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN KEFARMASIAN DI UPTD PUSKESMAS KUTA BLANG KABUPATEN BIREUEN - Fahma Shufyani; Mayang Sari; Muhammad Andry; Dwi Dominica (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; service quality is an important factor that can shape the trust of Health center patients to create loyalty and patient satisfaction with health services. The results of observations and brief interviews conducted with 11 outpatients at the Pharmacy of UPTD Kuta Blang Health Center, Bireuen Regency, found 6 patients who complained about services in daily operations, the lack of delivery of drug information and the limitations of drugs provided at the Health Center. Objectives; this study aimed to determine the level of patient satisfaction with pharmaceutical services at UPTD Kuta Blang Health Center, Bireuen Regency. Method; this is a descriptive survey method. The population of this study was 4,061 people with samples taken by using the slovin formula as many as 98 people. Analysis of the data used descriptive analysis. Result; the results of the study on the level of patient satisfaction with pharmaceutical services at UPTD Kuta Blang Health Center showed that the highest level of satisfaction was in the responsiveness dimension of 68.6%, physical evidence 67.1%, empathy 65.2%, assurance 62.7% and the last dimension of reliability is 62.2%. Conclusion; the conclusion of the study shows that the average percentage of patient satisfaction with pharmaceutical services at UPTD Kuta Blang Health Center, Bireuen Regency as a whole is 65.6% with the classification of satisfaction being dissatisfied.